The influence of nanosized zero-valent iron (nZVI) on the micropropagation, antioxidant activity, and phenolic compound content of cherry laurel (Prunus laurocerasus L.) - Kilic, Gul Cicek; Seker, Mine Gul; Gutul, Tatiana; Suzerer, Veysel; Dursun, Inan; Ciftci, Yelda Ozden (Springer, 2025)
Zero-valent iron nanoparticles (nZVIs) are reducing agents commonly used to purify pollutants in groundwater. However, recent reports have indicated that it also promotes plant growth and development. This study therefore investigated the effects of varying concentrations (12.5, 25, 50, 75, and 100 mg L-1) of nZVI on the micropropagation, total phenolic and flavonoid contents, and antioxidant activity of cherry laurel plants in in vitro tissue culture. The removal of the testa of the seed and the half-cut of the cotyledon were essential for successful germination. Following germination, the optimum 6-benzyladenine (BA) concentration for micropropagation was determined to be 1 mg L-1. Although the highest percentage of shoot tip proliferation (85.15%) was obtained with the inclusion of 75 mg L-1 nZVI in the culture medium, the maximum SFC index value (1.66), together with the highest contents of phenolics and flavonoids were obtained by adding 25 mg L-1 nZVI. This concentration also provided the best values for antioxidant activity. In addition, the maximum amount of chlorogenic acid (39.58 mg analyte g-1 extract), the main phenolic compound in cherry laurel, was also recorded with this concentration. The results revealed that the elevation of the concentration of nZVI in the culture medium led to a reduction in the positive effects on the growth, antioxidant activity and phenolic content of the plants. The optimum nZVI concentration was therefore determined to be 25 mg L-1. The present study has shown that nZVI has the potential to provide encouraging and alternative benefits in in vitro plant tissue culture.
Keywords: Cherry laurel; nZVI; Micropropagation; Phenolic compounds